2020
DOI: 10.1007/s11420-019-09689-9
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport and Sports-Specific Outcomes following Ulnar Collateral Ligament Reconstruction in Adolescent Athletes: A Systematic Review

Abstract: Background: The incidence of elbow injuries and ulnar collateral ligament (UCL) reconstruction in adolescent athletes is increasing. Knowledge and expectations of outcomes following this procedure are necessary for proper counseling and decision-making in this age group. Questions/Purposes: We sought to report patient-reported outcomes, rate of return to sport, and rate of complications and reoperation following UCL reconstruction in adolescent athletes. Methods: A systematic review was conducted for adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Upon close examination, we found that the studies that painted UCLR in a positive light tended to focus on excellent patient-reported outcomes and minimal complications while ignoring the beneficial effect of the intervention being compared, likely to show that UCLR is a safe and effective procedure overall. 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 In the few studies in which we identified spin that claimed the negative effect of UCLR, it was common for the study’s conclusion to overemphasize the findings of a slight decline in athletic performance to overshadow the high rate of return to play and claim an overall negative effect of the procedure. 22 , 39 Each of these studies was scored as having spin in category 13 (“Failure to specify the direction of the effect when it favors the control intervention”).…”
Section: Discussionmentioning
confidence: 99%
“…Upon close examination, we found that the studies that painted UCLR in a positive light tended to focus on excellent patient-reported outcomes and minimal complications while ignoring the beneficial effect of the intervention being compared, likely to show that UCLR is a safe and effective procedure overall. 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 In the few studies in which we identified spin that claimed the negative effect of UCLR, it was common for the study’s conclusion to overemphasize the findings of a slight decline in athletic performance to overshadow the high rate of return to play and claim an overall negative effect of the procedure. 22 , 39 Each of these studies was scored as having spin in category 13 (“Failure to specify the direction of the effect when it favors the control intervention”).…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews and meta-analyses exist in the literature that report on the incidence of RTS after UCL injury. 9 , 12 , 22 , 23 , 42 , 50 The available published data, however, often fail to specifically delineate the reasons for inability to RTS after UCL injury requiring reconstruction. This meta-analysis thus serves to supplement the literature with respect to why athletes undergoing elbow UCL reconstruction ultimately fail to return to their prior level of play.…”
Section: Discussionmentioning
confidence: 99%
“…Successful return to play following ulnar collateral ligament reconstruction was investigated in a systematic review by Haley et al 2021 reporting return to prior level of performance ranging between 66.67% and 91.4% with an average of 84.4% (39). Glogovac et al (41) reports patient-reported outcome scores and rates of return to sport were comparable in adolescent baseball players when compared with those reported in adult athletes. While return to sport following UCL reconstruction has been moderately successful in this population, identification of increased strain ratios and elasticity of the UCL may help identify athletes at risk for UCL injury in an attempt to avoid injury and subsequent surgical repair.…”
Section: Elbowmentioning
confidence: 99%
“…A number of studies have looked at factors related to injury in the youth baseball population over the past year ranging in topics from; early sport specialization (ESS) (12)(13)(14)(15)(16), pitch counts (17)(18)(19)(20)(21)(22)(23), prethrowing protocols (24,25), imaging findings (26), to body region-specific inquiries (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) in search for opportunities to reduce the risk of injury in this population. We will review a wide range of articles and their relevance to injury risk in this population.…”
Section: Literature Reviewmentioning
confidence: 99%